2013
DOI: 10.1104/pp.113.216598
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Tetraspanins Are Confined to Discrete Expression Domains and Cell Types in Reproductive Tissues and Form Homo- and Heterodimers When Expressed in Yeast      

Abstract: (L.C.B., P.Q., M.B., S.M.)Tetraspanins are evolutionary conserved transmembrane proteins present in all multicellular organisms. In animals, they are known to act as central organizers of membrane complexes and thought to facilitate diverse biological processes, such as cell proliferation, movement, adhesion, and fusion. The genome of Arabidopsis (Arabidopsis thaliana) encodes 17 members of the tetraspanin family; however, little is known about their functions in plant development. Here, we analyzed their phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
124
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(127 citation statements)
references
References 75 publications
3
124
0
Order By: Relevance
“…Expression levels of VCC and OPS affect both pattern complexity and the connectivity of veins in cotyledons. membrane or to the endoplasmic reticulum when expressed in protoplasts (Boavida et al, 2013). TET3 and a DUF1218-containing protein (AT1G15480) have been found to localize to the plasma membrane and to be enriched in plasmodesmata (Fernandez-Calvino et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of VCC and OPS affect both pattern complexity and the connectivity of veins in cotyledons. membrane or to the endoplasmic reticulum when expressed in protoplasts (Boavida et al, 2013). TET3 and a DUF1218-containing protein (AT1G15480) have been found to localize to the plasma membrane and to be enriched in plasmodesmata (Fernandez-Calvino et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The TET gene family consists of different clades with duplicated or triplicated members (Cnops et al, 2006;Wang et al, 2012;Boavida et al, 2013), showing diverging expression profiles (Figs. 1-3).…”
Section: Divergent Tet Expression Patterns Within Clades But Overlapmentioning
confidence: 99%
“…Mutations in animal tetraspanins result in severe defects, such as incurable blindness and impaired fertility (Kaji et al, 2002;Goldberg, 2006). In plants, phylogenetic studies identified 17 tetraspanin genes in the Arabidopsis (Arabidopsis thaliana) genome, most of which are duplicated (Cnops et al, 2006;Wang et al, 2012;Boavida et al, 2013). Mutants of the Arabidopsis TETRASPANIN1/ TORNADO2/EKEKO (TET1/TRN2) show defects in leaf lamina symmetry and venation pattern, root epidermal patterning (Cnops et al, 2000(Cnops et al, , 2006, peripheral zone identity of the SAM (Chiu et al, 2007), and megasporogenesis (Lieber et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the two sperm cell membranes are connected to each other through a tetraspaninenriched microdomain (8). Although all these physical connections presumably ensure that the vegetative nucleus and the sperm cells move in the pollen tube as a unit (known as the "male germ unit"), they also may provide a route for intercellular communication.…”
mentioning
confidence: 99%